A Quantitative Risk Analysis Due to Leakage of Ammonia Storage Tank at PUSRI IIB Factory - Aldillah Herlambang (Journal of Science, Technology, and Visual Culture, 2023)
Ammonia products in industry are usually stored in a cold state which is maintainedat a temperature of -33 C in a liquid state (refrigerated storage tank). One of thechemical industry companies that produces ammonia and has been established in themid-20th century is PT Pupuk Sriwijaya Palembang. One method that can be used topredict the scenario of an ammonia tank leak is by quantitative risk analysis. Thepurpose of this study is to identify the effect of the leakage of the ammonia storage tankat the Pusri IIB factory, calculate the concentration of ammonia scattered per unitdistance and calculate the distance affected by thermal radiation and toxic gases fromthe source of the leak, and compare the calculation results (manual) with the simulationresults with the device. ALOHA software. The tool used in the ALOHA simulation is alaptop with the following specifications: Lenovo Thinkpad T440p, Intel® CoreTM i5-400M, 8 GB RAM, 64-bit OS. The effects of ammonia storage tank leaks or accidentsdue to tank leaks that may occur after the ALOHA simulation are pool fire, BLEVE,toxic vapor cloud, and flammable area of vapor cloud. In scenario 1 for the impact ofpool fire thermal radiation (>10 kW/m2), the resulting red zone is 36 m. Probit analysisof the impact of pool fire was also carried out, with probit 1st degree burns it couldallow 261 people to be exposed at a distance of 45 meters and 14-16 people at adistance of 75 meters. For the BLEVE impact, the resulting red zone is up to 1.2 kmwith probit analysis of 1st degree burns in the dry season scenario, the possibility ofpeople being exposed is 9,007 people at a distance of 1,000 meters and 3,126-4,002people at a distance of 2,000 meters. While the spread of toxic gas (toxic vapor cloud),the red zone (ERPG-3) produced is 269 m. The worst impact for the occurrence of apool fire can reach 58 meters from the source of emission or tank leakage, BLEVEreaches 2.7 km, toxic area reaches 2.3 km, and flammable area reaches 60 meters. Therecommendations given in this study are checking the instruments on the tank,installing a lightning rod on the tank, and risk analysis is needed to anticipate tankleaks and avoid making densely populated settlements within 2 km of the ammoniatank.